The dynamics of a delayed generalized fractional-order biological networks with predation behavior and material cycle - Xie, Yingkang; Wang, Zhen; Shen, Hao; Li, Yuxia (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, a delayed generalized fractional-order biological networks with predation behavior and material cycle is comprehensively discussed. Some criteria of stability and bifurcation for the present system is presented. Moreover some results of two delays are obtained. Finally, some numerical simulations are presented to support the analytical results.